RESEARCH OF THE NATURE OF TRANSPORTATION IN UKRAINE BY ROAD TRANSPORT - Sazonets, O. M.; Lesnikova, I. Y. (Systems and Technologies, 2021)
The article emphasizes that motor transport in Ukraine is a service link of the entire national economy and plays an important role in the development of the countryʼs economy. The advantages and disadvantages of each type of transport are identified. It is noted that Ukraine is actively involved in world socio-economic processes. It is stated that in order to increase the efficiency of the transport system it is necessary to comprehensively update and modernize transport, which will include a set of measures for regulatory and legal support and the creation of a favorable investment climate, taking into account budgetary and non-budgetary investment. It was emphasized that the implementation of the transport strategy will contribute to the intensive improvement of the transport system, sustainable economic development and welfare of Ukrainians. The dynamics of road transport of passengers in Ukraine is presented and on its basis the forecast of a state of this branch for the next six years which is disappointing for our state is constructed. The reasons for this behavior of the forecast curve are given, the most significant of which are military actions in the East of the country. Ways to improve this situation are presented, first of all, by implementing certain provisions on transport, which are declared in the document on the association of Ukraine and the EU. The dynamics of cargo transportation by road in Ukraine is given and the forecast for the next six years, which is better than the previous one, is also built. The connection between Ukraineʼs GDP and road transport has been studied. The linear relationship is shown to be very weak. Other links checked. It is best to approximate this connection by a fifth degree polynomial. The solution of the system of equations is constructed, where the coefficients of the polynomial variable are determined. Here, the coefficient of determination is more acceptable than in the case of a linear relationship. The article identifies the main ways to solve the main problems of the motor transport industry, where the issue of tax burden, international freight, where it is necessary to introduce partial compensation for resource costs, reconstruction of roads, introduction of economic security management methods at transport enterprises.